Copyright and the New Materiality - Burk, Dan (AoIR Selected Papers of Internet Research, 2013)
Scholars in a variety of fields have recently begun to re-emphasize the centrality of matter in their exploration of the world. This “new materialism” seeks to traverse persistent analytical dichotomies between the ideal and the material. At the same time, copyright law has long rested upon a series of dualistic doctrinal structures, including the fundamental dichotomy between the immaterial “work” and its fixation in a physical “copy.” This distinction, which was never entirely coherent even in traditional media, has broken down in the face of digital instantiations of creativity. New materialism might offer copyright a path out of such unsustainable distinctions, by providing a viewpoint that traverses the artificial opposition of work and copy, recognizing the primacy of matter in the development of creative expression.